INTERPRETASI FAMILY VALUES PADA FILM KELUARGA CEMARA - Renata Winahyu, Maria; Sunarto, Sunarto; Bayu Widagdo, Muhammad (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
Film is one of the media used to spread information or messages to the public. Filmmakers have a vision and mission in making a film, not just for entertainment, but also to convey values that reflect social conditions and critique various aspects of life.